FIRST-TIME HOMEBUYERS’ INTERESTS IN USING PROPERTY CROWDFUNDING AS AN ALTERNATIVE FINANCING OPTION - Hon, Choong Chin; Sivanathan, Sheelah; Goh, Hong Lip; Low, Choon Wei (PLANNING MALAYSIA, 2021)
Property crowdfunding as an alternative financing option for first-time homebuyers was introduced by the Malaysian government during the presentation of the National Budget 2019. This platform was the first of its kind, and targeted fundraisers who were first-time homebuyers, i.e., those allowed to raise financial support for their home purchase via the platform. As the mechanism of the Malaysian property crowdfunding platform is new to homebuyers, this study aims to explore homebuyers’ interests to use property crowdfunding platform as an alternative financing option for the purchase of their first home. First-time homebuyers’ opinions were collected through face-to-face interviews, and content analysis was performed to analyse the obtained qualitative data. Key themes were identified and organised into three sections: (i) knowledge of the property crowdfunding; (ii) factors that motivated the use of the property crowdfunding and (iii) barriers that hindered the use of the property crowdfunding. These findings are expected to contribute toward the adoption of the property crowdfunding in Malaysia.